CoAl-layered double hydroxide nanosheets as an active matrix to anchor an amorphous MoSx catalyst for efficient visible light hydrogen evolution. Issue 26 (14th March 2018) - Min, Shixiong; Hou, Jianhua; Lei, Yonggang; Liu, Xiangyu; Li, Yanan; Xue, Yuan; Cui, Entian; Yan, Wenjun; Hai, Wanxiu; Wang, Fang
Abstract : CoAl LDH nanosheet supported MoS x efficiently catalyzes H2 evolution from an erythrosin B–triethanolamine molecular system under visible light (≥420 nm). Abstract : CoAl-layered double hydroxide nanosheets (CoAl-NSs) could serve as an active matrix to effectively anchor amorphous MoS x nanoparticles with high dispersion and the formation of an additional active "CoMoS" phase. The resulting CoAl-NSs/MoS x catalyst showed 13 times higher H2 evolution activity than free MoS x nanoparticles from an erythrosin B–triethanolamine (ErB–TEOA) system under visible light.